(untitled) (Indian Journal of Animal Production and Management, 2024)
The Chara Chambelli duck, indigenous to the foothills of the Himalayas, has been gaining attention for its potential as a valuable genetic resource in small-scale poultry production systems. This research paper aims to evaluate the performance of Chara Chambelli ducks in backyard rearing systems under agro-climatic condition of Darrang district of Assam. In the context of the NICRA project, the study was carried out on 400 Chara Chambelli ducks that were raised in backyard systems at the NICRA adopted village of Darrang district of Assam to look into their environmental suitability, productivity, and financial viability. By the time the ducks reached their fifth month of life, the overall weight of the male and female was measured at 1480.02 ± 18.14 grams and 1365.46 ± 14.90 grams respectively. The duck was 155.03± 9.18 days old on average when it laid its first egg. The data showed that the annual production of eggs was 169.12± 6.04 numbers and the weight of eggs at 63.98 ± 2.84 grams. For ducks and drakes, the corresponding benefit-cost ratios were 2.26 and 1.80. It was found that rearing Chara Chambelli ducks in backyard systems with low input traditional systems is more cost-effective than raising Assamese native ducks. Results indicate that Chara Chambelli ducks exhibit promising performance characteristics suitable for backyard rearing, contributing to sustainable livelihoods and biodiversity conservation efforts.